Phosphoglycerate mutase from Trypanosoma brucei is hyperactivated by cobalt in vitro, but not in vivo - Ahmad Fuad, Fazia Adyani (Royal Society of Chemistry, 2011)
Production of ATP by the glycolytic pathway in the mammalian pathogenic stage of protists from the genus Trypanosoma is required for the survival of the parasites. Cofactor-independent phosphoglycerate mutase (iPGAM) is particularly attractive as a drug target because it shows no similarity to the corresponding enzyme in humans, and has also been genetically validated as a target by RNAi experiments. It has previously been shown that trypanosomatid iPGAMs require Co2+ to reach maximal activity, but the biologically relevant metal has remained unclear. In this paper the metal content in the cytosol of procyclic and bloodstream-form T. brucei (analysed by inductively coupled plasma-optical emission spectroscopy) shows that Mg2+, Zn2+ and Fe2+ were the most abundant, whereas Co2+ was below the limit of detection (o0.035 mM). The low concentration indicates that Co2+ is unlikely to be the biologically relevant metal, but that instead, Mg2+ and/or Zn2+ may assume this role. Results from metal analysis of purified Leishmania mexicana iPGAM by inductively coupled plasma-mass spectrometry also show high concentrations of Mg2+ and Zn2+, and are consistent with this proposal. Our data suggest that in vivo cellular conditions lacking Co2+ are unable to support the maximal activity of iPGAM, but instead maintain its activity at a relatively low level by using Mg2+ and/or Zn2+. The physiological significance of these observations is being pursued by structural, biochemical and biophysical studies.